Hungarian Monitoring, 13 October 1990 . [Magyar rádiófigyelő], 1990. október 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Austrian parliamentary elections - UN Security Council compromise on the Jerusalem incident - Attempt against the German Interior Ministry - Soviet Union joins Interpol - Congress of Czech and Moravian communists - Octavio Paz wins Nobel Prize for Literature Domestic Affairs: - Checks on illegal immigrants - Plan for the utilization of empty Soviet barracks - Changes needed to criminal law Economy: - József Antall talks in Holland about transition to the market economy - Drop in foreign investors' enthusiasm Külpolitika: - Osztrák parlamenti választások - BT-kompromisszum a jeruzsálemi incidens ügyében - Merénylet a német belügyminiszter ellen - A Szovjetunió belépett az Interpolba - Cseh és morva kommunisták kongresszusa - Octavio Paz kapta az irodalmi Nobel-díjat Belpolitika: - Idegenrendészeti ellenőrzés - Terv az üresen maradó szovjet laktanyák felhasználására - Szükséges változások a büntetőjogban Gazdaság: - Antall József a piacgazdaságba való átmenetről beszél Hollandiában - A külföldi befektetői kedv megtorpanása